The Use of Oath Evidence and Its Implementation (Study in Surakarta Religious Court): English - Wibowo , Muhammad Kurniawan Budi; Kurnia Pradana, Aditya Fajri (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The evidence of the oath considering that the oath is directly related to God, then all the risks and consequences that arise will be felt alone to the reciter of the oath. What makes the most basic problem is that oath evidence is set at the end of various other evidence. The method of approach in this research is normative juridical, which is legal research conducted by examining library materials / secondary data as a basis for research by conducting a search for regulations related to the issues discussed. The results of research on oaths in Islamic law are the fulfilment of Allah's commandments that have a strong foundation. The oath by which one party binds the other party to the decision of a case, which is made orally in the presence of the opposing party and before the judge in the ongoing trial, is called the deciding oath/dicissoir.